ANALISIS PERAN KUALITAS LAYANAN, CITRA MEREK, DAN KEPUASAN PELANGGAN DALAM MENINGKATKAN LOYALITAS DAN KEPERCAYAAN PELANGGAN (STUDI KASUS PADA APLIKASI LIVIN’ BY MANDIRI) - Yullita Rochmawardani; Santi Rimadias (Journal of Accounting, Management and Islamic Economics, 2025)
This study analyze the influence of service quality and brand image on customer satisfaction and trust, and their impact on customer loyalty in using the mobile banking application Livin’ by Mandiri. The research employs a quantitative method with a descriptive approach, involving 150 active users of the Livin’ by Mandiri app. Data were collected via questionnaires and analyzed using structural equation modeling (PLS-SEM). The results indicate that service quality and brand image significantly affect customer satisfaction. Furthermore, customer satisfaction and trust positively influence customer loyalty. Customer trust was found to be a crucial mediating variable in strengthening the relationship between satisfaction and loyalty. These findings offer strategic insights for Bank Mandiri to enhance its digital service quality and foster long-term customer relationships.